Entre folhas e rezas: a presença do benzimento em Poço Verde-SE - Oliveira, Brunna Santos de (2024)
This dissertation aims to study healing practices carried by faith healers in the municipality of Poço Verde/SE. When reminiscing some of my childhood memories, I remember the day that I got in touch with a child who believed in the power of intention, of prayers and herbs. From that moment on, I decided to record this ancient and powerful practice. Our research can be justified by a scenario in which a biomedical hegemony becomes an authoritarian health model that ignores the autonomy of subjects and turns healthcare professionals into the exclusive holders of knowledge. Therefore, one can attest the need for analysis and record of popular wisdom concerned with health as a way of valuing these healing practices.We have the following guiding question: How these faith healers from Poço Verde/SE perform their healing practices? Our main goal is to analyze healing practices done by faith healers in the municipality of Poço Verde/SE. The specific goals are: to present historical, geographical and cultural aspects of the municipality; to link benzimento practice with medical field and spirituality; to describe benzimento ritual practiced by faith healers from Poço Verde. In order to understand medical development in Brazil and its link with benzimento practice, the theoretical studies were based on Hegenberg (1998), Figueiredo (2005) and Stancik (2009). The methodological approaches to oral memory and oral history took Borelli (1992), Halbwachs (1990) and Delgado (2003) as a basis. In turn, Oliveira (2014), Santos (2005) and Ilheo’s (2017) studies contributed to underlie the interview analysis. For that, we used a topical oral history research together with semi-structured interviews and audiovisual recordings. After finishing data collection, all the speeches were transcribed and analyzed according to Bardin’s data analysis technique. This work were submitted and approved by the Research Ethics Committee at Universidade Federal de Sergipe under CAAE n° 68432623.0.0000.5546. This dissertation is divided into three chapters. The first chapter gives an overview of the municipality chosen to carry out the research. In the second chapter, we contextualized the benzimento practice in Brazilian popular culture. We emphasized its importance as a way of caring for physical and spiritual health. Finally, in the third chapter, the results are directly showed where the interviewees are characterized and some aspects of theirs speeches are analyzed. In summary, interviewee’s stories highlight oral transmission as the main means of learning which indicates the generational continuity of benzimento practices. These faith healers’ practices and altars reveal a cultural hybridism that presents components of afro-brazilian religions, popular catholicism and spirituality.